2020
DOI: 10.12776/qip.v24i1.1401
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Statistical Process Control through PDCA Cycle to Improve Potential Capability Index of Drop Impact Resistance: A Case Study at Aluminum Beverage and Beer Cans Manufacturing Industry in Indonesia

Abstract: <p><strong>Purpose:</strong> The purposes of this study are first, to analyze why the <em>process capability index </em>(<em>Cpk</em>) for drop impact resistance (DIR) does not meet the specification or less than 1.33, and second, to find out what improvements should be made to make it meet the specification.</p><p><strong>Methodology/Approach:</strong> The methodology used was Statistical Process Control (SPC) through the PDCA cycle, supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
0
16
0
2
Order By: Relevance
“…Several problem-solving tools, such as PDCA (Plan, Do, Check, Action) and DMAIC (Define-Measure-Analyze-Improve-Control), are widely used today. PDCA is a traditional approach used to solve medium-scale problems and implies that the PDCA cycle must be restarted in the Act phase to ensure continuous improvement, as in (Sunadi, Purba and Hasibuan, 2020) which uses the PDCA method to increase the process capability. In concept, however, the PDCA can still be enhanced again, so that the process's ability can even be better.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several problem-solving tools, such as PDCA (Plan, Do, Check, Action) and DMAIC (Define-Measure-Analyze-Improve-Control), are widely used today. PDCA is a traditional approach used to solve medium-scale problems and implies that the PDCA cycle must be restarted in the Act phase to ensure continuous improvement, as in (Sunadi, Purba and Hasibuan, 2020) which uses the PDCA method to increase the process capability. In concept, however, the PDCA can still be enhanced again, so that the process's ability can even be better.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They analyzed and found out the solutions for the process capability index meeting the specification. The results showed that PDCA is a useful and effective method for improving packaging quality [15]. The benefits of practicing PDCA in planning, testing, and developing changes for target purposes make it become a well-known technique in the quality management field [16][17][18][19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the consideration of increasingly rapid evolution, organizations must compete with strict attention to the factors that affect the process. Therefore, companies must continue to pay attention to the delivery time limit, costs to be incurred, and the quality of their products so that they are in line with market demand [6]. Quality management methods are successfully used in business process development and need to be continuously improved in terms of adapting business models so that companies become more competitive [7].…”
Section: Introductionmentioning
confidence: 99%